1978
DOI: 10.1042/bj1690509
|View full text |Cite
|
Sign up to set email alerts
|

The binding of porphyrins by ligandin

Abstract: Spectrophotometric and equilibrium-dialysis measurements show that ligandin (glutathione S-transferase B, EC 2.5.1.18) binds monomeric porphyrins at a single site with association constants in the range 10(4)-10(6) litre/mol at pH 7.0. Binding affinities are paralleled by the tendencies of the porphyrins to aggregate, increasing in the order: uroporphyrins I and III less than coproporphyrins I and III approximately haematoporphyrin less than protoporphyrin IX. From this it is deduced that the hydrophobic effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(35 citation statements)
references
References 23 publications
1
34
0
Order By: Relevance
“…The first GST described was originally identified as 'ligandin' due to its ability to interact covalently and noncovalently with various compounds that are not substrates for enzymatic activity, including steroids, thyroid hormones, bile acid, bilirubin, and heme (Litwack et al, 1971;Tipping et al, 1978;Danielson and Mannervik, 1985). While the ligand-binding function remains unclear, sequestering molecules may serve a regulatory role, preventing cytotoxic ligands from interacting with their targets.…”
Section: Gsts As Regulators Of the Map Kinase Pathwaymentioning
confidence: 99%
“…The first GST described was originally identified as 'ligandin' due to its ability to interact covalently and noncovalently with various compounds that are not substrates for enzymatic activity, including steroids, thyroid hormones, bile acid, bilirubin, and heme (Litwack et al, 1971;Tipping et al, 1978;Danielson and Mannervik, 1985). While the ligand-binding function remains unclear, sequestering molecules may serve a regulatory role, preventing cytotoxic ligands from interacting with their targets.…”
Section: Gsts As Regulators Of the Map Kinase Pathwaymentioning
confidence: 99%
“…This was done by referring to typical standard spectra assigned previously to a monomeric form, another type of monomeric form protonated at the inner nitrogen atoms of monomeric porphyrin (abbreviated as a N-protonated monomer), and a dimeric form. [8][9][10][11][12] Relative concentrations of individual species were calculated with a computer program developed in our laboratory by fitting the sum of the fractions of the standard spectra of the pure forms to the spectrum observed.…”
Section: Methodsmentioning
confidence: 99%
“…9,10,12) First, we used CP, because this porphyrin was in a monomer-dimer equilibrium at around a neutral pH, 8,10,11) and expected to show strong pH-dependence. To obtain information on the state of the aggregation of CP, we measured absorption spectra at various pHs.…”
Section: Ph-dependence Of Absorption Spectra Of Cpmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we used a luminol chemiluminescence method 9,10 and found that it could quantify H2O2 even in the presence of a high concentration of porphyrin. Using the present method, we demonstrated how the chemical properties of porphyrins, especially their aggregation in an aqueous solution, [11][12][13] influenced the photogeneration of H2O2.…”
mentioning
confidence: 99%